2021
DOI: 10.1155/2021/5512143
|View full text |Cite
|
Sign up to set email alerts
|

Pelvic Chondrosarcoma Treated by En Bloc Resection with Patient-Specific Osteotomy Guides and Reimplantation of the Extracorporeally Irradiated Bone as an Osseocartilaginous Structural Orthotopic Autograft: A Report of Two Cases with Description of the Surgical Technique

Abstract: Primary tumors of the pelvis are considered difficult to treat due to the complex anatomy and the proximity of important neurovascular structures. The surgical armamentarium for the treatment of these tumors has evolved with the help of cutting-edge technology from debilitating hemipelvectomies to solutions such as precise resections guided by patient-specific instruments or computer navigation and reconstruction by modular prostheses, 3D-printed custom-made implants, or orthotopic autograft reimplantation aft… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 37 publications
0
3
0
Order By: Relevance
“…The complexity of the resection also varied between one and four cutting planes. The analysis was based on workflow explanations in the articles ( Wong et al, 2016 ; García-Sevilla et al, 2021 ) or visual assessments ( Cernat et al, 2016 ; Jentzsch et al, 2016 ; Gkagkalis et al, 2021 ). It showed that the design workflow of SCGs for pelvic tumor resections has rarely been detailed, justifying our methodology-based original article.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The complexity of the resection also varied between one and four cutting planes. The analysis was based on workflow explanations in the articles ( Wong et al, 2016 ; García-Sevilla et al, 2021 ) or visual assessments ( Cernat et al, 2016 ; Jentzsch et al, 2016 ; Gkagkalis et al, 2021 ). It showed that the design workflow of SCGs for pelvic tumor resections has rarely been detailed, justifying our methodology-based original article.…”
Section: Discussionmentioning
confidence: 99%
“…However, there does not seem to be any set methodology for designing such guides ( Numajiri et al, 2018 ). Recent publications, using pelvic surgical guides, showed a wide variety of designs with no clearly classified or standardized features ( Wang et al, 2017 ; Evrard et al, 2019 ; Siegel et al, 2020 ; Gkagkalis et al, 2021 ) . The only feature that is common to any surgical guide is the positioning, which uses the negative shape of the bone.…”
Section: Introductionmentioning
confidence: 99%
“…However, there does not seem to be any set methodology for designing such guides (Numajiri et al, 2018). Recent publications, using pelvic surgical guides, showed a wide variety of designs with no clearly classified or standardized features (Wang et al, 2017;Evrard et al, 2019;Siegel et al, 2020;Gkagkalis et al, 2021). The only feature that is common to any surgical guide is the positioning, which uses the negative shape of the bone.…”
Section: ) Magnesium Decomposition Increases Bone Tissue Formationmentioning
confidence: 99%
“…The complexity of the resection also varied between one and four cutting planes. The analysis was based on workflow explanations in the articles (Wong et al, 2016;García-Sevilla et al, 2021) or visual assessments (Cernat et al, 2016;Jentzsch et al, 2016;Gkagkalis et al, 2021). It showed that the design workflow of SCGs for pelvic tumor resections has rarely been detailed, justifying our methodology-based original article.…”
Section: Scg Workflowmentioning
confidence: 99%
“…Three-dimensional (3D)-printing technology has been introduced in the field of orthopedic surgery, including its application in total joint arthroplasty, the treatment of malunion, and the reconstruction of bone defects due to trauma or bone tumors [ 1 , 2 , 3 ]. Treating complex comminuted fractures requires extensive surgical experience and anatomical knowledge, and patients with malunion could require osteotomy to correct the deformity and relieve pain [ 4 ].…”
Section: Introductionmentioning
confidence: 99%